FARMERS' PERCEPTIONS OF SELECTING OIL PALM PLANTS DURING RE-PLANTING IN KAMPUNG DELIMA JAYA, KERINCI KANAN DISTRICT, SIAK REGENCY - Latifa Siswati; Asgami Putri (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
Oil palm is a plant that has high value as a source of income for the community. But oil palm plants have a maximum age to get optimal results. If after the production age the plant produces but will not get optimal results. The purpose of this study was to determine the characteristics of farmers who are carrying out re-planting activities and to determine the perception of farmers in choosing oil palm as a crop or business during the re-planting period in Delima Jaya Village, Kerinci Right District, Siak Regency. Sampling in this study was carried out using the purposive sampling technique with the sampling criteria being farmers who carried out re-planting activities and chose oil palm cultivation. The number of samples in this study amounted to 100 people. The analysis used in this research is factor analysis. From the results of this study, it can be said that the perception of farmers in choosing re-planting activities is a high selling price (X5) with a Communalities value of 82.8. Based on the results obtained, it can be concluded that what determines a farmer in carrying out tre-planting activities is the selling price of the oil palm. This is because the older the oil palm plant, the lower the selling price because the oil contained in TBS is less. So that farmers prefer to replant their oil palm plants compared to not replanting.